A prospective pilot study on the incidence of post-operative lymphedema in women with endometrial cancer - Elizabeth E. Hopp; Janet L. Osborne; Deborah K. Schneider; Claudia J. Bojar; Denise S. Uyar (Gynecologic Oncology Reports, 2016)
To determine the incidence of lower-extremity lymphedema after surgical therapy including lymphadenectomy in endometrial cancer patients using standardized leg measurements. Also, to determine additional risk factors for the development of lymphedema and to study the effect of lymphedema on one's quality of life. In this prospective cohort study, patients with the diagnosis of endometrial cancer who were to undergo definitive surgical management were evaluated pre-operatively and followed post-operatively over the course of two years. Standardized leg measurements were performed by the same individuals at six time-points. Subjects also completed a standardized quality-of-life survey at each time-point. The incidence of lymphedema in 39 women with endometrial cancer using a standardized leg measurement protocol was 12.8% with lymphedema defined as a 20% increase in post-operative leg measurements. There was no significant association between the development of lymphedema and the number of pelvic or para-aortic lymph nodes removed, medical comorbidities, or surgical approach (p > 0.05). Of the five patients who met criteria for lymphedema, only one had worsening quality-of-life concerns post-operatively on the FACT-En, version 4, survey. This is the first prospective study using standardized leg measurements to calculate the incidence of post-operative lymphedema in endometrial cancer. Medical comorbidities, surgical approach, number of lymph nodes removed, and location of lymph nodes removed did not appear to affect the development of lymphedema in this cohort. A prospective, multicenter trial is needed to confirm these findings and to further assess the impact of lymphedema on one's quality of life.